1989
DOI: 10.1073/pnas.86.19.7590
|View full text |Cite
|
Sign up to set email alerts
|

Persistent poliovirus infection of human neuroblastoma cells.

Abstract: Two human neuroblastoma cell lines were persistently infected with poliovirus strains of all three serotypes. In persistently infected IMR-32 cells, which were studied in greatest detail, viral antigens were present in most cells, and over a 9-month period virions were found in the medium at high titers. Persistently infected cells were resistant to superinfection by Sabin 1, 2, and 3 poliovirus but sensitive to coxsackievirus B3. The viruses recovered from persistently infected cells were studied for conserva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
55
0
2

Year Published

1992
1992
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(60 citation statements)
references
References 31 publications
(28 reference statements)
3
55
0
2
Order By: Relevance
“…Several picornaviruses including CVB3 have been shown to establish persistent infections in vivo and in vitro in several diseases and cell types (5)(6)(7)(8)(9)(10)(11)(12)(13)(14). Persistent Coxsackieviral infection in the murine heart is qualitatively distinct from acute viral infection.…”
Section: Introductionmentioning
confidence: 99%
“…Several picornaviruses including CVB3 have been shown to establish persistent infections in vivo and in vitro in several diseases and cell types (5)(6)(7)(8)(9)(10)(11)(12)(13)(14). Persistent Coxsackieviral infection in the murine heart is qualitatively distinct from acute viral infection.…”
Section: Introductionmentioning
confidence: 99%
“…However, the possibility of nonlytic release of poliovirus and other picornaviruses has been suggested from numerous reports of persistently infected cell lines that continuously secrete infectious particles. 17,18,14,19 Even more convincingly, when polarized Caco-2 cultures, growing as intact monolayers, were infected with poliovirus, newly synthesized virus was shown to emerge only from the apical surface. 14 Assays showed that the monolayer remained intact, arguing that a non-lytic, and polarized, exit route of unknown origin had been utilized.…”
mentioning
confidence: 99%
“…Other researchers have reported that the coxsackie B virus could also use the decay accelerating factor (DAF, CD55; Bergelson et al, 1995;Shafren et al, 1995), a 70-kDa protein that protects cells from complement-mediated lysis. Early studies revealed that one of the most important factors determining the ability of these viruses to establish a persistent infection in vitro is the change of receptor usage compared with their parental strains or with the prototype strains (Colbere-Garapin et al, 1989;Zhang and Racaniello, 1997;Duncan et al, 1998). This change of receptor usage has been shown to be because of amino acid substitutions in the capsid proteins (Duncan and Colbere-Garapin, 1999;Schmidtke et al, 2000).…”
Section: Discussionmentioning
confidence: 99%